A-113 Evaluation of a Recognition Trial for the Symbol Digit Modalities Test as a Performance Validity Measure in Monolingual and Bilingual Traumatic Brain Injury Survivors. (30th August 2021) - Munoz, Isabel; Lopez-Hernandez, Daniel W; Rugh-Fraser, Rachel A; Bichlmeier, Amy; Baez, Abril J; Nordberg, Bethany A; Saravia, Sarah; Litvin, Pavel Y; Budding, Deborah; Vespa, Paul M; Hovda, David A; Fuster, Joaquin M; et al.
Abstract: Objective: Research shows that traumatic brain injury (TBI) patients perform worse than healthy comparisons (HC) on the Symbol Digit Modalities Test (SDMT). We evaluated cut-off scores for a newly developed recognition trial of the SDMT as a performance validity assessment in monolingual and bilingual TBI survivors and HC adults. Method: The sample consisted of 43 acute TBI (ATBI; 24 monolinguals; 19 bilinguals), 32 chronic TBI (CTBI; 13 monolinguals; 19 bilinguals), and 57 HC (24 monolinguals; 33 bilinguals) participants. All participants received standardized administration of the SDMT. None of the participants displayed motivation for feigning cognitive deficits. Results: The HC group outperformed both TBI groups on the demographically adjusted SDMT scores, p = 0.000, ηp2 = 0.24. An interaction emerged in SDMT scores where monolingual ATBI outperformed bilingual ATBI and bilingual CTBI outperformed monolingual CTBI, p = 0.017, ηp2 = 0.06. No differences were found in the SDMT recognition trial. Both Bichlmeier and Boone's suggested cut-off scores had different failure rates in ATBI (Bichlmeier: 77%; Boone: 37%), CTBI (Bichlmeier: 69%; Boone: 19%), and HC (Bichlmeier: 56%; Boone: 26%). For the monolingual group (Bichlmeier: 66%; Boone: 36%) and the bilingual group (Bichlmeier: 66%; Boone: 21%). Finally, chi-squared analysis revealed monolingual TBI had greater failure rates than the bilingual ATBI. Conclusion: Bichlmeier's proposed cut-off score resulted in greater failure rates in TBI survivors compared to Boone's suggested cut-off score. Furthermore, monolingual ATBI were influenced more by Bichlmeier's cut-off score than the bilingual ATBI group, although the reason for this finding is unclear and requires additional study with a larger sample size.